What is the best treatment strategy for primary spontaneous pneumothorax? A retrospective study. (September 2019) - Chikaishi, Yasuhiro; Kanayama, Masatoshi; Taira, Akihiro; Nabe, Yusuke; Shinohara, Shinji; Kuwata, Taiji; Hirai, Ayako; Imanishi, Naoko; Ichiki, Yoshinobu; Tanaka, Fumihiro
Abstract: Background: Several treatment strategies are available for primary spontaneous pneumothorax (PSP). Surgical procedures are also performed in patients with PSP without an absolute indication for surgery. This study was performed to investigate the best treatment strategy for PSP by comparison of the recurrence rate. Materials and methods: From January 2006 to December 2013, 149 patients with PSP aged ≤50 years were treated in our institution. We reviewed the recurrence rate of PSP for each treatment strategy and evaluated the association between the recurrence rate of PSP with the clinicopathological characteristics. We also compared the surgery and non-surgery groups. Results: A significant difference in the PSP recurrence rate was found between the surgery and non-surgery groups (22% vs. 52%, respectively; p < 0.001), patients aged ≥22 and < 22 years (16% vs. 44%, respectively; p < 0.001), and smokers and nonsmokers (13% vs. 43%, respectively; p < 0.001). There were also significant differences in the multivariate analysis (p < 0.001, p = 0.050, and p = 0.001, respectively). In the surgery group, the PSP recurrence rate was significantly different between patients aged ≥22 and < 22 years (7% vs. 38%, respectively; p < 0.001) and smokers and nonsmokers (5% vs. 33%, respectively; p = 0.002). No significant differences were found in the non-surgery group. Conclusions: In the surgical treatment of PSP, it is desirable that smokers stop using tobacco and that patients are ≥22 years old. Moreover, when surgery is being considered, the best timing seems to be when air leakage is present because the air leakage sites can be resected. Highlights: Younger patients had a higher recurrence rate than older patients. Smokers had a lower recurrence rate than nonsmokers. When we select the surgical treatment of PSP, it is desirable that smokers stop using tobacco and that patients are older.